Auditoría de gestión a la empresa Diario la Hora, regional Los Ríos, año 2014 - Rodríguez Medranda, Tania Gabriela (2016)
The present research thesis entitled: AUDITORÍA DE GESTIÓN A LA EMPRESA DIARIO LA HORA REGIONAL LOS RÍOS, AÑO 2014, the same that was developed in the middle of written communication Journal Regional Time Rivers located in the canton of Quevedo, Los Rios Province located on the streets June Guzmán and Tenth building Ipersa, the management audit arises from the need with greater control of the activities to have reasonable information at the time that required for the correct decision so that this will allow us to know the reality of activities to avoid any negative situation that could affect the normal development of activities that are linked to the performance indicators that are related to internal control activities as mediator that meet the objectives of the company. For this research project induction methods, deductive, interview and questionnaires that helped us obtain relevant information in order to obtain findings and issue findings and recommendations of the research product were used. the internal control system of the company was assessed by COSO I, which could determine the extent of deficiencies with a risk index of 18.07% control is considered (bass); confidence level of 81.93% confidence; an inherent risk of 27% and a risk of 0.39% Audit it is considered acceptable according to ISA 200 Audit Principles (audit risk and materiality). It takes into consideration the level of efficiency is 70% efficiency 98% and 70% effectiveness is considered good. According to the results the audit report for the decision is issued.